Learning Styles of Preclinical Medical Students - (:unkn) unknown (HACETTEPE UNIV, 2014)
The aim of the present study was to determine the learning styles of preclinical medical students and to investigate the Interrelationships among the learning style variables. In order to determine the learning style, Vermunt's Inventory of Learning Styles (1994) was administered to the 289 students. Chi-square test, factor analysis and multiple regression analysis were used for statistical analysis. In factor analysis, four learning styles were identified among students, named as meaning-, application-, reproduction- and un-directed learning. The results of multiple regression analyses showed that significant predictive variables for the deep and concrete cognitive processing strategies were self-regulation and constructivist and pragmatist learning approaches; for stepwise cognitive processing was external regulation and passive reproductive learning approach; for self-regulation was constructivist, for external regulation was passive reproductive and lastly, for lack of regulation was passive reproductive learning approaches. With further studies, it is important to investigate different patterns of students' learning processes and to develop process-oriented medical education programs that are compatible with learners' properties.
Keywords: Learning strategies; learning orientations; process-oriented instruction